STRATEGI PEMBELAJARAN BA DI SMP UNISMUH MAKASSAR TALASALAPANG (Az-Zaida: Jurnal Ilmu Multidisiplin, 2026)
Arabic language learning at the junior high school level requires appropriate strategies to ensure that learning objectives are achieved optimally. Differences in students backgrouns, limited instructional time, and low learning motivation often become challenges in the Arabic learning process. Therefore, teachers are required to implement affective, creative, and student-centered learning strategies that align with students characteristic. This study aims to describe  theArabic language learning strategies applied at SMP UNISMUH makassar talasalapang and to identify the supporting and inhibiting factors in their impelementation. This research employed a descriptive research design. The research subjects consisted of Arabic language teachers and students at SMP UNISMUH makassar talasalapang. Data were collected through observation, interviews, and documentation. The collected data were analyzed through data reduction, data display, and conclusion drawing to obtain a comprehensive description of the implemented learning strategies. The results of the study indicate that Arabic language learning strategies at SMP UNISMUH makassar talasalapang include the use of communicative methods, drill methods, question and answer acivites, and the utilization of simple learning media such as textbooks, whiteboards, and visual media. Teachers also combine vocabulary learning (mufrodat) with simple speaking practice to enhance students comprehension and Arabic language skills.